1980
DOI: 10.1149/1.2129717
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Electrodeposition of Nickel‐Cobalt‐Tungsten Alloys

Abstract: Electrodeposition of nickel-cobalt-tungsten alloys containing 2-51% Ni, 18-79% Co, 5-62% W has been carried out from a citrate bath under different conditions of concentration of electrolyte, current density, pH, and temperature. Tungsten content in the deposit was found to increase with an increase in its content in the bath and also with an increase in pH, temperature, and current density. Surface morphology of the deposits was examined by scanning electron microscopy and crystal structure by x-rays. Microha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Lowe et al [6] found that the hardness of Ni-W alloys is three times higher than that of pure electrodeposited Ni. In addition, the hardness is found to increase with increase in W content in the alloy as reported by Singh et al [7]. It is a wellestablished fact that W cannot be electrodeposited from aqueous electrolytes, but can be codeposited with iron group metals such as nickel to form an alloy [8,9].…”
Section: Introductionsupporting
confidence: 56%
“…Lowe et al [6] found that the hardness of Ni-W alloys is three times higher than that of pure electrodeposited Ni. In addition, the hardness is found to increase with increase in W content in the alloy as reported by Singh et al [7]. It is a wellestablished fact that W cannot be electrodeposited from aqueous electrolytes, but can be codeposited with iron group metals such as nickel to form an alloy [8,9].…”
Section: Introductionsupporting
confidence: 56%
“…The results show that keeping Co concentrations constant, the highest Ni concentrations in the bath lead to higher deposition of Ni and minor amounts of W and Co in the coating alloy. And when Ni concentration is constant, higher Co concentrations in the bath result in lower deposition of Ni and greater deposition of W and Co. Singh et al also found that increasing the concentration of metals in the bath increases concentration in the alloy, however they have not studied the correlation between these variables . The coating failures showed that independent of the concentration of Ni and W in the deposit, canyon formation is observed, as seen in Figures a and b or uncoated deeper regions (in black) as presented in Figure c and d. Both types of failure are not observed in the micrograph of Figure , showing that with the chemical composition of 48 % Ni, 12 % Co, 40 % W, a more uniform coating is obtained.…”
Section: Resultsmentioning
confidence: 89%
“…Studies on Ni‐Co have shown that alloy microstructure as well as its properties strongly depends on the content of Co and also the processing parameters, such as bath composition, pH, and temperature . According to Singh et al, on their studies of ternary alloy Ni‐Co‐W, increasing the content of metals in the electrochemical bath increases their percentage in the alloy. These results regarding the influence of the bath on alloy composition are important because for some alloys, electrodeposition techniques, and bath compositions, increasing the metal in the bath does not ensure the metal increases its percentage in the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 11). Also, Singh et al [30] reported that the microhardness of Ni-W deposits increased with an increase in tungsten content in the alloy. In the present work, it is observed that the XRD peaks ( Figure 27) that correspond to the Ni in Ni-W solid solution were broad and shifted to lift side.…”
Section: Reduction Of Nio-wo 3 Mixtures and Niwomentioning
confidence: 98%